Dynamic dielectric properties and the γ transition of bromine doped polyacrylonitrile (eXPRESS Polymer Letters, 2007)
Based on monitoring the γ process (the lowest temperature-relaxation) in polyacrylonitrile (PAN) by dynamic dielectric spectroscopy, new evidence for the formation of a charge transfer complex between bromine dopants and nitrile groups is presented. The experimental work is carried out on PAN and nitrile polymerized PAN with and without bromine doping and the effects of these factors on the γ process are measured. Nitrile polymerization results in diminishing of the γ process and in a 15% increase in its activation energy, whereas bromine doping produces splitting of the original γ process in PAN – coupled with a significant activation energy increase – and its complete disappearance in nitrile polymerized PAN. Both the splitting of the γ process and the higher activation energy reflect bromine-nitrile adduct formation..